Optimal Design of PID Controller for Load Frequency Control using Harmony Search Algorithm - D. K. Sambariya; Seema Shrangi (Institute of Advanced Engineering and Science, 2017)
This paper deals with soft computing technique, used for tuning PID controller. Controller tuned with a harmony search algorithm is used for controlling the frequency and Tie-line power responses of a non reheat two area power system. Step load perturbation has been given in both areas simultaneously. The dynamic results obtained by the proposed controller are compared with PID controller of recent published paper. The performance of the controllers is simulated using MATLAB/Simulation software. The results of tuned PID are compared with conventional controller on the basis of settling-time, peak over-shoot and peak under-shoot. Proposed PID gives better results than the conventional controller. The comparative resultsalso tabulated as a comparative performance.